Preparation and in vitro Evaluation of Inclusion Complexes of Nelfinavir with Chemically Modified ?-cyclodextrins - Hiremath, Shivanand; Godge, Ganesh (Dhaka University Journal of Pharmaceutical Sciences, 2013)
Nelfinavir is a poorly water-soluble antiretroviral drug with relatively low bioavailability. In the present study, the practically insoluble drug, nelfinavir (NFV) and its inclusion complexes with hydroxypropyl-?-cyclodextrin (HP-?-CD) were investigated to improve the aqueous solubility and the dissolution rate of the drug, thus enhancing its bioavailability. The phase solubility diagram with HP-?-CD was classified as AL-type at all temperatures investigated, indicating the formation of higher order complexes. The apparent complexation constants (K1:1) calculated from phase solubility diagram were 145.49, 188.45 and 255.54 M-1 at 25, 37 and 45 ± 0.5°C, respectively. Aqueous solubility and dissolution studies indicated that the dissolution rates were remarkably increased; this could be mainly attributed to the improved solubility and dissolution associated with inclusion complex between drug and HP- ? -CD. Absence of endothermic and characteristic diffraction peaks corresponding to NFV was observed for the inclusion complex in DSC and PXRD. FT-IR study indicated that the presence of intermolecular hydrogen bonds between NFV and HP-?-CD in inclusion complex, resulting in the formation of amorphous form. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14558 Dhaka Univ. J. Pharm. Sci. 11(2): 107-116, 2012 (December)